2017
DOI: 10.1111/jphs.12209
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicines: a cross-sectional study among hypertensive patients in Iraq

Abstract: Objectives The purpose of this study was to assess the use, predictors and patient's seeking behaviour of complementary and alternative medicines (CAM) in hypertension and evaluate patient's perception of CAM adverse effects. Methods A cross‐sectional questionnaire‐based study was conducted among hypertensive patients from May to December 2015. A convenience sample technique was adopted to recruit patients attending two major teaching hospitals in the capital city Baghdad, Iraq. A total of 400 valid responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
2
12
2
Order By: Relevance
“…The prevalence of herbal use in this study (80.2%) was the highest when compared with findings presented in other studies from Middle Eastern areas [5,17,18] and the United States [19]. The majority of previous studies reported a higher rate of use of herbal medicines among hypertensive patients [20][21][22].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The prevalence of herbal use in this study (80.2%) was the highest when compared with findings presented in other studies from Middle Eastern areas [5,17,18] and the United States [19]. The majority of previous studies reported a higher rate of use of herbal medicines among hypertensive patients [20][21][22].…”
Section: Discussioncontrasting
confidence: 49%
“…Moreover, the only associated health-related characteristic was the patient's disease state, including specifically hypertension. On the contrary, other studies showed an association with some demographic variables such as educational level or marital status as reported by Ibrahim et al [17]. Another survey in Turkey showed a significant association with almost all demographic variables considered [21].…”
Section: Discussionmentioning
confidence: 78%
“…Based on a country's cultural characteristics, rates of use of CAM methods in the USA, the Far East, and Europe range between 9% and 80%. 2,5,6 Notably, the use of herbal medications are the most common methods. 6,7 Several studies have examined the benefits of CAM in diabetes mellitus, hypertension, malignancy, and rheumatic diseases; however, only few have explored its use in chronic viral hepatitis (CVH).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Several studies have examined the benefits of CAM in diabetes mellitus, hypertension, malignancy, and rheumatic diseases; however, only few have explored its use in chronic viral hepatitis (CVH). 5,7,8 Viral hepatitis is a chronic disease wherein the efficacious treatment may be either extensive or limited. Notably, there are approximately 240 million patients with chronic hepatitis B (CHB) worldwide, and 170 million with chronic hepatitis C (CHC).…”
Section: Introductionmentioning
confidence: 99%
“…Positive outcomes are reported in many developing countries compared with the negative results reported by the industrialized world [11]. In Iraq, information and exact statistics on the prevalence of CAM use specifically cupping therapy is not yet available [13]. Interest in wet-cupping among the public to treat various hematological disorders, particularly polycythemia, has grown considerably in recent years.…”
mentioning
confidence: 99%